2017
DOI: 10.1007/s13139-017-0480-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Dual Time Point FDG PET/CT and Clinical Prognostic Indexes in Patients with High Grade Lymphoma: a Pilot Study

Abstract: RI extracted from DTPFP had a significant relationship to extranodal involvement, staging, IPI, and revised IPI. MVDI showed significant negative correlation with RI. Further large scale studies are warranted to support and extend these preliminary results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…Some studies have reported that RI is related to the biological characteristics of breast cancer [ 9 , 21 , 22 ]. RI has also been reported to be correlated with prognosis in patients with lung cancer, cholangiocarcinoma, and lymphoma [ [23] , [24] , [25] ]. However, only one study has reported a relationship between RI and prognosis in patients with breast cancer [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that RI is related to the biological characteristics of breast cancer [ 9 , 21 , 22 ]. RI has also been reported to be correlated with prognosis in patients with lung cancer, cholangiocarcinoma, and lymphoma [ [23] , [24] , [25] ]. However, only one study has reported a relationship between RI and prognosis in patients with breast cancer [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some reported that 18 F-FDG uptake in malignancy continued to increase until approximately 4-5 h after injection, but the uptake decreased in the benign lesion 30 min after the injection [18,28]. Furthermore, the ΔSUV max % was correlated with the grade of malignancy in lung cancer and lymphoma [29,30]. Although the usefulness of ΔSUV max % was generally considered acceptable, few reports have been published on its relationship with the prognosis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Les deux é tudes, explorant les capacité s de l'acquisition retardé e/DTP à diffé rencier des ganglions bé nins d'adé nopathies lymphomateuses, ont montré des ré sultats contradictoires quant à son apport supplé mentaire vs une acquisition classique [153,154] et d'autres articles ont montré des liens entre les paramè tres issus de l'acquisition DTP et l'indice de prolifé ration, l'index pronostique international et le bilan d'extension tumoral dont la pré sence d'une atteinte extra-ganglionnaire [156,157].…”
Section: Caracte´risation Malin/be´ninunclassified